A Third-Generation Lipid Emulsion that Contains n–3 Long-Chain PUFAs Preserves Retinal Function in Parenterally Fed Neonatal Piglets. Issue 11 (12th October 2016) - Turner, Justine M; Sauvé, Yves; Suh, Miyoung; Wales, Paul W; Wizzard, Pamela; Goruk, Susan; Field, Catherine J
Abstract: Background: Preterm neonates and those with intestinal failure require prolonged parenteral nutrition (PN) during a critical time of early central nervous system maturation. Conventional lipid emulsions fed to preterm neonates lack n–3 (ω-3) long-chain polyunsaturated fatty acids (LC-PUFAs; >20 carbon chain in length). Recently, fish oil lipid emulsions have been developed that provide both n–6 (ω-6) and n–3 LC-PUFAs, precursors of very long–chain PUFAs (VLC-PUFAs; >24 carbon chain in length). Objective: Our objective was to determine the effect of fish oil lipid on retinal function in neonatal piglets fed total PN with the use of the lipid emulsions available in clinical practice. We hypothesized that fish oil–containing parenteral lipid would preserve retinal function more than conventional parenteral lipid. Methods: Male neonatal piglets (2–5 d of age) were fed isonitrogenous (16 g · kg −1 · d −1 ), isocaloric (1.1 MJ · kg −1 · d −1 ) PN that varied only in the lipid emulsion: Intralipid or SMOFlipid at 10 g · kg −1 · d −1 ( n = 8/group). Retinal function was assessed after 14 d of treatment by recording electroretinograms under various light intensity conditions. Retinas were then harvested for histology and to determine fatty acid composition. Results: Electroretinogram intensity response curves showed greater photoreceptor a-wave amplitude in piglets fed SMOFlipid than in those fed Intralipid (percentage), for postsynaptic depolarizing bipolar cell b-waves (percentage) and for flicker electroretinogram amplitudes (percentage) ( P < 0.05). Compared with those fed Intralipid, SMOFlipid-fed piglets had greater retinal total n–3 LC-PUFAs (15.7% compared with 18.4%; P = 0.04) and n–3 VLC-PUFAs (0.9% compared with 1.5%; P = 0.02), whereas Intralipid-fed piglets had greater total n–6 LC-PUFAs (13.1% compared with 10.5%; P < 0.01) and n–6 VLC-PUFAs (0.7% compared with 0.5%; P = 0.01). Histologically, retinas were indistinguishable between groups. Conclusions: In a neonatal piglet model of PN feeding, the inclusion of fish oil–based n–3 LC-PUFAs in the lipid emulsion leads to their accretion and endogenous elongation to VLC-PUFAs in the retina, which is associated with better retinal function.